2020
DOI: 10.1055/a-1268-7312
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic findings of gastric lesions in patients with eosinophilic gastrointestinal disorders

Abstract: Background and study aims Eosinophilic gastrointestinal disorders are classified into eosinophilic esophagitis, eosinophilic gastritis, eosinophilic gastroenteritis, and eosinophilic colitis according to the site of eosinophilic infiltration. Although well established in eosinophilic esophagitis, endoscopic findings in eosinophilic gastritis and eosinophilic gastroenteritis with regard to gastric lesions have not been clearly described. The aim of this study was to identify endoscopic findings of gastric lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…The white granular patches observed in our case are rare in EG but have been reported [10, 11]. Patchy discoloration, which appeared similar to atrophic gastritis in our case, has also been reported [11].…”
Section: Discussion/conclusionsupporting
confidence: 76%
See 1 more Smart Citation
“…The white granular patches observed in our case are rare in EG but have been reported [10, 11]. Patchy discoloration, which appeared similar to atrophic gastritis in our case, has also been reported [11].…”
Section: Discussion/conclusionsupporting
confidence: 76%
“…Endoscopic findings in EG are normal in a majority of cases, with various possible changes including erythema, erosions, fold thickening, nodules, and friability [10]. The white granular patches observed in our case are rare in EG but have been reported [10, 11]. Patchy discoloration, which appeared similar to atrophic gastritis in our case, has also been reported [11].…”
Section: Discussion/conclusionsupporting
confidence: 63%
“…We postulate that the increased detection is related to the prospective data acquisition, experience of the CEGIR investigators, and systematic inclusion of multiple features. It should be noted that one Japanese study that carefully reassessed endoscopic images of the stomach reported higher prevalence of endoscopic abnormalities compared with studies relying on endoscopic reports (6). Of note, this study also identified mucosal cracks (fissures), rings, and white exudate similar to features described in EoE that were not included in EG-REFS (6).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that one Japanese study that carefully reassessed endoscopic images of the stomach reported higher prevalence of endoscopic abnormalities compared with studies relying on endoscopic reports (6). Of note, this study also identified mucosal cracks (fissures), rings, and white exudate similar to features described in EoE that were not included in EG-REFS (6). The heterogeneity in the prevalence of endoscopic findings may be related to varied demographics, diagnostic criteria, and use of active medical/diet therapies at the time of the endoscopies across studies.…”
Section: Discussionmentioning
confidence: 99%
“…These data are confirmed by studies of some authors and indicate the need for histological examination [20]. However, despite this fact, there is a constant search for macroscopic changes in the mucous membrane of the gastrointestinal tract and their justification in terms of clinical, laboratory, and microscopic data, and it is proposed to take into account a number of features that are statistically significant [21,22]. Therefore, currently, mucosal biopsy is a reliable diagnostic method for the detection of characteristic changes and eosinophilic infiltration [23].…”
Section: Figure 2 the Mucous Membrane Of The Gastric Antrum In A Child From Group 1 With Clinical Manifestations Of Food Hypersensitivitymentioning
confidence: 83%